2017
DOI: 10.5152/npa.2017.19393
|View full text |Cite
|
Sign up to set email alerts
|

LDL Subclasses in Ischemic Stroke: A Risk Factor?

Abstract: Introduction: Seven low-density lipoprotein (LDL) subclasses are identified, and smaller LDL particles are associated with an increased risk for cardiovascular events. However, there is limited data about the relationship between the acute ischemic stroke (AIS) subtypes and LDL subclasses. The aim of our study is to investigate the relationship between AIS subtypes and LDL subclasses. Methods: This study consisted of 110 AIS patients and 60 healthy controls. Stroke patients were classified according to the TOA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…In terms of certain LDL particles, our findings are different from the other two studies by Zeljkovic et al and Kayran et al The former Serbia group examined LDL subclasses in 200 AIS patients as well as 162 controls, showing that AIS patients had ignificantly more LDL III and IVb subclasses (sd-LDL), but less large LDL I and II particles [16]. The latter, however, recruited 110 AIS patients and 60 healthy controls from Turkey in the study, and reported that apart from LDL-3 and LDL-4, the level of large LDL-2 particles was also significantly higher in AIS patients [17]. The distribution of large LDLs (LDL-1 and LDL-2) between AIS and control group is in controversy though, all three studies demonstrated a significant elevation of sd-LDLs, especially LDL-3 and LDL-4 levels in the AIS patients.…”
Section: Discussionmentioning
confidence: 97%
“…In terms of certain LDL particles, our findings are different from the other two studies by Zeljkovic et al and Kayran et al The former Serbia group examined LDL subclasses in 200 AIS patients as well as 162 controls, showing that AIS patients had ignificantly more LDL III and IVb subclasses (sd-LDL), but less large LDL I and II particles [16]. The latter, however, recruited 110 AIS patients and 60 healthy controls from Turkey in the study, and reported that apart from LDL-3 and LDL-4, the level of large LDL-2 particles was also significantly higher in AIS patients [17]. The distribution of large LDLs (LDL-1 and LDL-2) between AIS and control group is in controversy though, all three studies demonstrated a significant elevation of sd-LDLs, especially LDL-3 and LDL-4 levels in the AIS patients.…”
Section: Discussionmentioning
confidence: 97%
“…Limited studies exploring the relationship between LDL subclasses and AIS subtypes have been done. The atherogenic effect of sdLDL particles on carotid atherosclerosis is well known 35) . Higher levels of sdLDL-C and LDL-C were found in LAA, SAO, marker to predict ischemic stroke risk.…”
Section: Logistic Regression Models For Predicting the Risk And Prognmentioning
confidence: 99%
“…Besides, LDL-3, LDL-studies by Zeljkovic et al and Kayran et al The former Serbia group examined LDL subclasses in 200 AIS patients as well as 162 controls, showing that AIS patients had signi cantly more LDL III and IVb subclasses (sd-LDL), but less large LDL I and II particles [16]. The latter, however, recruited 110 AIS patients and 60 healthy controls from Turkey in the study, and reported that apart from LDL-3 and LDL-4, the level of large LDL-2 particles was also signi cantly higher in AIS patients [17]. The distribution of large LDLs (LDL-1 and LDL-2) between AIS and control group is in controversy though, all three studies demonstrated a signi cant elevation of sd-LDLs, especially LDL-3 and LDL-4 levels in the AIS patients.…”
Section: Discussionmentioning
confidence: 91%